3D FSE Cube and VIPR-aTR 3.0 Tesla magnetic resonance imaging predicts canine cranial cruciate ligament structural properties. (March 2016) - Racette, Molly; Al saleh, Habib; Waller, Kenneth R.; Bleedorn, Jason A.; McCabe, Ronald P.; Vanderby, Ray; Markel, Mark D.; Brounts, Sabrina H.; Block, Walter F.; Muir, Peter
Highlights: We performed ex-vivo 3D 3.0 Tesla MRI and mechanical testing of the canine stifle. Data were collected using isotropic high resolution sequences. Cranial cruciate ligament yield load and load to failure were correlated with ligament volume determined by MRI. Cranial cruciate ligament structural properties were not related to MRI median grayscale value. 3D MRI may be useful for monitoring cranial cruciate ligament structural properties in clinical studies. Abstract: Estimation of cranial cruciate ligament (CrCL) structural properties in client-owned dogs with incipient cruciate rupture would be advantageous. The objective of this study was to determine whether magnetic resonance imaging (MRI) measurement of normal CrCL volume in an ex-vivo canine model predicts structural properties. Stifles from eight dogs underwent 3.0 Tesla 3D MRI. CrCL volume and normalized median grayscale values were determined using 3D Fast Spin Echo (FSE) Cube and Vastly under-sampled Isotropic PRojection (VIPR)-alternative repetition time (aTR) sequences. Stifles were then mechanically tested. After joint laxity testing, CrCL structural properties were determined, including displacement at yield, yield load, load to failure, and stiffness. Yield load and load to failure ( R 2 = 0.56, P < 0.01) were correlated with CrCL volume determined by VIPR-aTR. Yield load was also correlated with CrCL volume determined by 3D FSE Cube ( R 2 = 0.32, P < 0.05). Structural properties were not related to median grayscale values. Joint laxity and CrCL stiffness were not related to MRI parameters, but displacement at yield load was related to CrCL volume for both sequences during testing ( R 2 > 0.57, P < 0.005 ) . In conclusion, 3D MRI offers a predictive method for estimating canine CrCL structural properties. 3D MRI may be useful for monitoring CrCL properties in clinical trials.